Study of Physics-Based preconditioning with High-order Galerkin discretization for hyperbolic wave problems - Courtès, Clémentine; Franck, Emmanuel; Helluy, Philippe; Oberlin, Herbert (ESAIM. Proceedings and surveys, 2016)
In this article, we detail the construction of a physics-based preconditioner. The Schur decomposition is the key point of the method which is tested on two hyperbolic systems : acoustic wave equations and shallow water equations without source term. Some conserved properties between preconditoner and initial operator are discussed, especially the propagation speeds of a plane wave. Dans cet article, nous détaillons la construction d’un préconditioneur basé sur la physique sous-jacente des équations considérées. La décomposition de Schur est le point clé de la méthode, qui sera testée sur deux systèmes hyperboliques : les équations des ondes acoustiques et les équations de Saint Venant sans terme source. Nous étudions certaines propriétés conservées entre le préconditioneur et l’opérateur initial, notamment les vitesses de propagation d’une onde plane.